Guinea : Joint Staff Advisory Note on the Extended Poverty Reduction Strategy Paper 2011-12 and the 2011 Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
The attached Joint Staff Advisory Note (JSAN) on the Implementation of the Poverty Reduction Strategy Paper for Guinea, prepared jointly by the staffs of the World Bank and the IMF, was distributed with the member country's Poverty Reduction Strategy Paper (PRSP) to the Executive Boards of the two institutions. The objective of the JSAN is to provide focused, frank, and constructive feedback to the country on progress in implementing its Poverty Reduction Strategy (PRS).